2015
DOI: 10.21608/ejnf.2015.105111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Selenium Enriched Micro-Algae Supplementation on Growth Performance and Anti-Oxidative Status of Rabbits Under High Ambient Temperature in Summer Season

Abstract: his study was carried out to investigate the effect of different levels of dietary selenium enriched micro-algae supplementation on growth performance, carcass characteristics, blood biochemical constituents, and anti-oxidative status of rabbits under Egyptian summer conditions. Total of 90 male growing New Zealand White rabbits, six weeks old with an average initial body weight 757.5 g were used in this study. Rabbits were randomly allocated to six experimental groups, with 15 rabbits in each group. The first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 45 publications
4
5
0
Order By: Relevance
“…The effect of Zn-Se-Sp was positive in hot carcass weight, dressing% and total edible parts compared to the control group. The current results are in line with those of Hassan et al [ 36 ] who stated that rabbits on diets supplied with Se-algae at level of 0.5 mg/kg diet increased hot carcass weight, dressing% and total edible parts%. Moreover, Hassan et al [ 35 ] indicated that Zn-Sp supplementation at 50, 75 and 100 mg/kg diet increased hot carcass weight, dressing and total edible parts% compared with the rabbits fed the control diet.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The effect of Zn-Se-Sp was positive in hot carcass weight, dressing% and total edible parts compared to the control group. The current results are in line with those of Hassan et al [ 36 ] who stated that rabbits on diets supplied with Se-algae at level of 0.5 mg/kg diet increased hot carcass weight, dressing% and total edible parts%. Moreover, Hassan et al [ 35 ] indicated that Zn-Sp supplementation at 50, 75 and 100 mg/kg diet increased hot carcass weight, dressing and total edible parts% compared with the rabbits fed the control diet.…”
Section: Discussionsupporting
confidence: 93%
“…The present study showed a positive influence of the supplemented diets on plasma biochemistry indices. These outcomes are consistent with those of Hassan et al [ 36 ] who mentioned that rabbit consumed diet including 50, 70 and 100 mg/kg had high total protein and HDL. In addition, the dietary Zn- and Se-enriched Sp or their combination had no significant effect of A/G ratio, albumin levels and activities of AST and ALT.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations